Scenarios and strategies for clean power development in the Philippines - De Guzman, Remife Villarino (2006)
The Philippine government, in its Renewable Energy Policy Framework, aims to aggressively pursue development of renewable energy potential and increase the country's renewable energy base capacity in ten years. The Philippine Power Development (PDP) Plan, however, do not specify renewable capacity additions to support such government's goal. This study, which aimed to determine if and how the country can pursue development and utilization of renewable and clean energy, assessed the available resources and technologies and created power development scenarios that prioritize the utilization of such energy resources. Two scenarios were examined in this study. The first scenario allowed wind power plants to take up to 5% of the peak demand; while, the second scenario permitted up to 20% wind power penetration. These scenarios were evaluated in terms of installed capacity, energy generation, reliability, environmental emissions, and levelized generating cost and compared with the would-be-performance of the power sector (assuming that the capacity additions were fossil-based). The historical performance of the Philippine power sector was likewise reviewed. Strategies to achieve the scenarios and further clean and renewable energy development and utilization in the country conclude this study.